Comparisons of Positron Emission Tomography/Computed Tomography and Ultrasound Imaging for Detection of Internal Mammary Lymph Node Metastases in Patients With Breast Cancer and Pathologic Correlation by Ultrasound‐Guided Biopsy Procedures. (1st August 2015) - An, Yeong Yi; Kim, Sung Hun; Kang, Bong Joo; Lee, Ah Won
Abstract : Objectives: To compare the diagnostic performance of [ 18 F]fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) and ultrasound imaging (US) with pathologic results obtained by US‐guided biopsy and to evaluate the role of US in detecting internal mammary lymph node (LN) metastases in patients with breast cancer. Methods: Between January 2008 and December 2012, 37 patients with breast cancer (median age, 51.4 years; range, 40–79 years) underwent US‐guided biopsy for suspected internal mammary LN metastases. Medical records, radiologic images, and reports were reviewed and correlated with pathologic results. Results: The positive internal mammary LN metastasis rate was 78.4%. All biopsies were performed safely without major complications. Only 8.1% of obtained samples were unsatisfactory. There were statistically significant differences in lesion size ( P = .0002), standardized uptake value on PET/CT ( P = .0015), biopsy methods ( P = .002), and specimen adequacy ( P = .007) between metastatic and benign groups. Of the clinical factorsreviewed, only concurrent distant metastasis was correlated with internal mammary LN metastasis ( P < .0001). Sensitivities for detecting internal mammary LN metastases were 76.7%, 96.7%, and 92.9% for initial US examinations, initial US combined with second‐look US for initially missed cases, and PET/CT, respectively ( P = .017). In a subgroup analysis, the only significant difference found was in sensitivities between initial and combined US ( P = .019). In a receiver operating characteristic curve analysis, the area under the curve for PET/CT using standardized uptake criteria (0.87) was higher than that for US using size criteria (0.83); however, this difference was not significant. Conclusions: Although PET/CT is the best noninvasive method for evaluating internal mammary LN metastases, US is also useful if internal mammary LN evaluation is routine during standard US surveillance of patients with breast cancer. Additionally, US‐guided biopsies could be performed immediately on any suspected metastases and yield a high positive rate without serious complications.